Comparison of the biomechanical properties of a ventral cervical intervertebral anchored fusion device with locking plate fixation applied to cadaveric canine cervical spines. Issue 7 (3rd September 2013) - Schöllhorn, Bernhard; Bürki, Alexander; Stahl, Christina; Howard, Judith; Forterre, Franck
Abstract Objective To evaluate fixation properties of a new intervertebral anchored fusion device and compare these with ventral locking plate fixation. Study Design In vitro biomechanical evaluation. Animals Cadaveric canine C4–C7 cervical spines (n = 9). Methods Cervical spines were nondestructively loaded with pure moments in a nonconstraining testing apparatus to induce flexion/extension while angular motion was measured. Range of motion (ROM) and neutral zone (NZ) were calculated for (1) intact specimens, (2) specimens after discectomy and fixation with a purpose‐built intervertebral fusion cage with integrated ventral fixation, and (3) after removal of the device and fixation with a ventral locking plate. Results Both fixation techniques resulted in a decrease in ROM and NZ (P < .001) compared with the intact segments. There were no significant differences between the anchored spacer and locking plate fixation. Conclusion An anchored spacer appears to provide similar biomechanical stability to that of locking plate fixation.